Leflunomide plus low-dose prednisone in patients with progressive IgA nephropathy: a multicenter, prospective, randomized, open-labeled, and controlled trial. Issue 1 (1st January 2021) - Ni, Zhaohui; Zhang, Zhen; Yu, Zanzhe; Lu, Fuming; Mei, Changlin; Ding, Xiaoqiang; Yuan, Weijie; Zhang, Wei; Jiang, Gengru; Sun, Min; He, Liqun; Deng, Yueyi; et al.
Abstract: Background: Immunoglobulin A nephropathy (IgAN) is the most common cause of glomerulonephritis worldwide, and the optimal approach to its treatment remains a significant challenge. Methods: We did a prospective, randomized, open-labeled, multicenter, controlled trial, comprised of 3-month run-in, 12-month treatment, and 12-month follow-up phases. After 3-month run-in phase, patients with biopsy-confirmed IgAN at risk of progression were randomly allocated to LEF plus low-dose prednisone (LEF + prednisone group) or conventionally accepted-dose prednisone [prednisone(alone) group] Our primary outcome was 24-h urine protein excretion (UPE) and secondary outcomes were serum albumin (sALB), serum creatinine (Scr), and eGFR. Safety was evaluated in all patients who received the trial medications. Results: One hundred and eight patients [59 in LEF + prednisone group, 49 in prednisone (alone) group]were enrolled and finished their treatment and follow-up periods. There is no significant difference in the baseline level between the two groups. Compared with baseline, both groups showed a significant decrease in 24-h UPE ( p  < 0.01) and increase in sALB ( p  < 0.01), with stable Scr and eGFR throughout the 12-month treatment period. What's more, these effects were sustained through the 12-month follow-up period. However, there was no difference in 24-h UPE, sALB, Scr, and eGFR between the two groups ( p  > 0.05). At 12 months, a difference in overall response rate, relapsing rate, and incidence of adverse events between the two groups was not significant. Conclusions: The efficacy and safety of LEF plus low-dose prednisone and conventionally accepted-dose prednisone in the treatment of progressive IgAN are comparable.